Institutions and Regional Economic Growth: An Assessment of Mexican Regional Strategies 1970-2000 - Maria Luisa Decuir-Viruez (European Regional Science Association (ERSA), 2006)
Different factors have been included in order to explain the causes of growth and the disparities observed in the last century. This paper examines the role of institutional factors in the growth rates observed among the 32 states in Mexico in the period 1970-2000. The institutional elements considered are the "strategies" of local governments, in order to assess if the active strategies (those that are participative, open to global economies and less dependent upon central authorities) have better results in terms of growth than the passive type (those that are dependent on central authorities and have restricted external links). Following on from the documents presented at the ERSA Annual Conferences of 2003/4/5, this paper presents the final assessment of the relationship between institutional elements and growth. This includes identification and measurement of the institutional elements (strategies) through Principal Components Analysis (PCA); and its evaluation with growth using Ordinary Least Square Regressions (OLS). The PCA results identified components related to hard and soft institutional elements (strategies and social networks). Meanwhile, the OLS results suggest that institutions matter; in the case of Mexico, the strategies taken by regional governments in the period 1970-2000 have had some influence in their paths of growth and levels of investment. Furthermore, after 1985 there is evidence that the active strategies (which have substituted the national regional policy) are related to a positive performance, in contrast to the passive type.
Keywords: 330